Teachers’ understanding of technology usage in rural schools - Sepadi, Medwin; Kgaphola, Tukiso; Molapo, Karabo (Frontiers in Education, 2025)
This study aimed to examine rural teachers’ understanding and implementation of technology integration in under-resourced South African schools. Using a qualitative single-case study design, the research employed semi-structured interviews and focus group discussions with four purposively sampled teachers, analyzed through the TPACK framework. Key findings revealed three critical challenges: (1) insufficient technological knowledge and training among educators, (2) severe resource limitations, including inadequate devices and unreliable infrastructure, and (3) systemic misalignment between available technologies and curriculum requirements. The study further identified how these barriers interact to constrain effective pedagogical integration of technology. These findings have important implications for educational policy and practice, suggesting the need for: comprehensive professional development programs targeting technological-pedagogical skills; improved resource allocation and infrastructure support; and stronger alignment between technological tools and curricular objectives. The research contributes both empirical insights from a typically underrepresented rural context and practical recommendations for enhancing digital education in resource-constrained environments.